Deep learning-based transformation of H&E stained tissues into special stains - Kevin de Haan (Nature Portfolio, 2021)
Performing multiple histological stains on a biopsy can be costly and time consuming. Here the authors present a method for the digital transformation of H&E stained tissue into special stains (e.g., PAS, Masson’s Trichrome and Jones silver stain), and demonstrate that it improves diagnoses over the use of H&E only.